إمكانات الإصلاح الدينيّ - هل ثمَّة مساءلة حقيقية حول جذور التطرف والإرهاب؟ - الخالدي, محمد عبدالله (lark, 2018)
How can we talk about religious reform in an environment full of extremism and prejudice? What can reform represent among the right, the left, and the center? Is it a preservation of pure origin? Is it a paradox of what cannot be relevant to our reality? Is it a review of the problematic aspects only? Is the task of religious reform a religious or non-religious mission? How? Is reform possible without the need for political power or is it impossible without it?